Vibration-damping rubber composition for electric vehicles and vibration-damping rubber member for electric vehicles

The vibration-proof rubber composition for electric vehicles, comprising diene rubber, high-hydrogen surface-active carbon black, and low-iodine carbon black, addresses the challenge of achieving low dynamic magnification in high rigidity areas, ensuring effective vibration reduction and durability for electric vehicles.

JP2025054958APending Publication Date: 2025-04-08SUMITOMO RIKO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023164216
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing vibration-proof rubber compositions for electric vehicles struggle to achieve low dynamic magnification in areas with high rigidity, despite efforts to control carbon black content and particle properties.

Method used

A vibration-proof rubber composition for electric vehicles is formulated with diene rubber, surface-active carbon black with high hydrogen content, and carbon black with low iodine adsorption, optimized in mass ratios to achieve low dynamic magnification and high durability.

Benefits of technology

The composition effectively achieves low dynamic magnification in high rigidity regions while maintaining excellent durability, making it suitable for electric vehicle applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054958000001
    Figure 2025054958000001
Patent Text Reader

Abstract

To provide a vibration-damping rubber composition for electric vehicles and a vibration-damping rubber member for electric vehicles which are capable of achieving low dynamic magnification in a region with high rigidity (a large static spring constant).SOLUTION: A vibration-damping rubber composition for electric vehicles contains the components (A) to (C) below. (A) is a diene rubber. (B) is a surface-active carbon black having a value (Hc), which is defined as the amount of hydrogen generated per gram of carbon black when heated to 1980°C, of 4500 ppm or more. (C) is carbon black with an iodine adsorption amount of 20 g / kg or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anti-vibration rubber composition for electric vehicles and an anti-vibration rubber member for electric vehicles. [Background technology]

[0002] Anti-vibration rubber compositions are used in automobiles to reduce vibration and noise. Such anti-vibration rubber compositions are required to have high rigidity and high strength in their vulcanizates (anti-vibration rubber members) and to suppress vibration transmission, so that the value of the dynamic magnification [dynamic spring constant (Kd100) / static spring constant (Ks)] is required to be small (low dynamic magnification). Electric vehicles are heavier than gasoline vehicles, so anti-vibration rubber members are required to have high durability. Therefore, it is important to reduce the dynamic magnification in the region of higher rigidity (large static spring constant). Conventionally, measures to reduce the dynamic magnification have been taken, for example, by using carbon black as a reinforcing agent in anti-vibration rubber compositions and controlling factors such as the amount of carbon black blended, particle size, and structure. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 7037986 Summary of the Invention [Problem to be solved by the invention]

[0004] However, it is difficult to achieve a low dynamic magnification in a higher rigidity (large static spring constant) range simply by controlling factors such as the amount of carbon black blended, particle size, structure, etc., as has been the case in the past.

[0005] The problem to be solved by the present invention is to provide an anti-vibration rubber composition for electric vehicles and an anti-vibration rubber member for electric vehicles that can achieve a low dynamic magnification in a high rigidity (large static spring constant) region. [Means for solving the problem]

[0006] In order to solve the above problems, the anti-vibration rubber composition for electric vehicles according to the present invention contains the following components (A) to (C). (A) Diene rubber (B) Surface-activated carbon black, which has a hydrogen emission amount (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C. (C) Carbon black with an iodine adsorption of 20 g / kg or less

[0007] The total amount of (B) and (C) may be 60 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of (A). The mass ratio of the content of (C) to (B) may be 0.5 or more and 2.0 or less. (A) may be one or more kinds selected from natural rubber, butadiene rubber, styrene butadiene rubber, isoprene rubber, and chloroprene rubber. The static spring constant Ks of the anti-vibration rubber composition for electric vehicles according to the present invention may be 700 N / mm or more and 1000 N / mm or less.

[0008] The anti-vibration rubber member for electric vehicles according to the present invention is formed from a vulcanizate of the anti-vibration rubber composition for electric vehicles according to the present invention.

[0009] (1) The anti-vibration rubber composition for electric vehicles according to the present invention contains the following components (A) to (C): (A) Diene rubber (B) Surface-activated carbon black, which has a hydrogen emission amount (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C. (C) Carbon black with an iodine adsorption of 20 g / kg or less

[0010] (2) In the above (1), the total amount of (B) and (C) may be 60 parts by mass or more and 100 parts by mass or less per 100 parts by mass of (A).

[0011] (3) In the above (1) or (2), the mass ratio of the content of (C) to the content of (B) is preferably 0.5 or more and 2.0 or less.

[0012] (4) In any one of the above (1) to (3), the (A) may be one or more rubbers selected from the group consisting of natural rubber, butadiene rubber, styrene butadiene rubber, isoprene rubber, and chloroprene rubber.

[0013] (5) In any one of the above (1) to (4), the static spring constant Ks of the anti-vibration rubber composition for electric vehicles may be 700 N / mm or more and 1000 N / mm or less.

[0014] (6) The anti-vibration rubber member for electric vehicles according to the present invention is constituted by a vulcanizate of the anti-vibration rubber composition for electric vehicles according to any one of (1) to (5) above. Effect of the Invention

[0015] According to the anti-vibration rubber composition for electric vehicles according to the present invention, since it contains the above-mentioned components (A) to (C), it is possible to achieve a low dynamic magnification in a high rigidity (large static spring constant) region.

[0016] Here, when the total amount of (B) and (C) is 60 parts by mass or more and 100 parts by mass or less per 100 parts by mass of (A), it is easy to achieve a low dynamic magnification in a high rigidity (large static spring constant) region.

[0017] When the mass ratio of the content of (C) to that of (B) is 0.5 or more and 2.0 or less, a low dynamic magnification is achieved in a high rigidity (large static spring constant) region, while excellent durability is also achieved.

[0018] When the (A) is one or more types selected from natural rubber, butadiene rubber, styrene butadiene rubber, isoprene rubber, and chloroprene rubber, it is easy to achieve a low dynamic magnification in a high rigidity (large static spring constant) region.

[0019] If the static spring constant Ks is 700 N / mm or more and 1000 N / mm or less, it is suitable for use in an electric vehicle.

[0020] Furthermore, since the anti-vibration rubber member for electric vehicles according to the present invention is composed of a vulcanizate of the anti-vibration rubber composition for electric vehicles according to the present invention, a low dynamic magnification can be achieved in a high rigidity (large static spring constant) region. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The anti-vibration rubber composition for electric vehicles and the anti-vibration rubber member for electric vehicles according to the present invention will be described in detail below.

[0022] The anti-vibration rubber composition for electric vehicles according to the present invention (hereinafter sometimes simply referred to as anti-vibration rubber composition) contains the following components (A) to (C). (A) Diene rubber (B) Surface-activated carbon black, which has a hydrogen emission amount (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C. (C) Carbon black with an iodine adsorption of 20 g / kg or less

[0023] The diene rubber (A) is the main component of the rubber component of the anti-vibration rubber composition. The main component of the rubber component means a component that occupies 50% by mass or more of the total rubber component of the anti-vibration rubber composition. The anti-vibration rubber composition is greatly affected by the properties of the diene rubber (A), which is the main component of the rubber component. Examples of the diene rubber (A) include natural rubber (NR), butadiene rubber (BR), styrene-butadiene rubber (SBR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR). These are used alone or in combination as the diene rubber (A). Among these, natural rubber is preferably used from the viewpoint of achieving both strength, durability, and low dynamic magnification. In addition, the combined use of natural rubber (NR) and butadiene rubber (BR) is preferable because it further reduces the dynamic magnification. The butadiene rubber (BR) is more preferably a terminal-modified butadiene rubber (BR). From the viewpoint of reducing the dynamic magnification, the mixing ratio of natural rubber (NR) and butadiene rubber (BR) is preferably NR / BR=100 / 0 to 70 / 30 by mass, and more preferably NR / BR=90 / 10 to 70 / 30.

[0024] The terminal-modified butadiene rubber (B) is a butadiene rubber whose molecular terminals are modified with an appropriate compound. As the modifier, metal salts such as tin tetrachloride (see "Japan Rubber Association Journal," Vol. 63, No. 5 (1990), pp. 27-33) have been known. It is also known to use a lactam compound as a modifier (for example, Nagata, "Japan Rubber Association Journal," Vol. 62, No. 10 (1989), pp. 38-48). The modifier is not particularly limited, but by blending lactam-modified butadiene rubber with natural rubber, particularly excellent improvement in vibration-proofing properties is observed.

[0025] The surface active carbon black (B) has the effect of lowering the dynamic magnification without lowering the static spring constant or hardness of the vibration-proof rubber composition. The high rigidity region refers to a region where the static spring constant Ks (N / mm) is 700N / mm or more. More preferably, the static spring constant Ks (N / mm) is 750N / mm or more. As described above, the surface active carbon black (B) has a value (Hc) of 4500ppm or more, calculated as the amount of hydrogen generated per gram of carbon black when heated to 1980°C. If the Hc is 5000ppm or more, it is preferable because the surface activity is more excellent. The amount of hydrogen is derived from hydrogen atoms of organic groups, such as hydroxyl groups and carboxy groups, that are covalently bonded to carbon atoms of the carbon black. Since the surface active carbon black (B) has many polar functional groups, it has a strong interaction with the diene rubber (A) and reduces friction between the diene rubber (A) and the surface of the surface active carbon black (B). This is believed to contribute to lowering the dynamic magnification in the high rigidity region where the static spring constant is large.

[0026] The measurement of the amount of hydrogen is carried out, for example, as follows. That is, first, in order to remove the adsorbed components of the carbon black, 20 mg of carbon black, which has been degassed and dried in a vacuum dryer at 125°C for 4 hours, is placed in a tin capsule, and a high-sensitivity hydrogen analyzer (EMGA-621 manufactured by Horiba, Ltd., using a TCD detector) is used to thermally decompose the carbon black in a graphite crucible at 1980°C for 70 seconds. Then, the generated gas is passed through a high-temperature oxidizing agent, a room-temperature oxidizing agent, a carbon dioxide removing agent, and a desiccant by a carrier gas (inert argon gas) at a constant flow rate (400 ml / min), and separated in a column. Then, the hydrogen gas obtained is quantified by a detector (thermal conductivity method).

[0027] The surface active carbon black (B) may be used alone or in combination of two or more kinds, so long as it has the above-mentioned hydrogen amount.

[0028] From the viewpoints of durability and low dynamic magnification, the surface active carbon black (B) preferably has an iodine adsorption of 14 g / kg or more and 28 g / kg or less. The iodine adsorption of the carbon black is a value measured in accordance with JIS K 6217-1 (method A). Moreover, from the viewpoints of durability and low dynamic magnification, the surface active carbon black (B) preferably has a DBP absorption of 118 ml / 100 g or more and 132 ml / 100 g or less. The DBP absorption of the carbon black is a value measured in accordance with JIS K 6217-4.

[0029] As described above, the carbon black (C) has an iodine adsorption of 20 g / kg or less. The carbon black (C) is a surface-inactive carbon black. By using the carbon black (C) having an iodine adsorption of 20 g / kg or less together with the surface-active carbon black (B), a low dynamic magnification can be achieved in a high rigidity (large static spring constant) region. The iodine adsorption of the carbon black (C) is more preferably 10 g / kg or more and 20 g / kg or less, and even more preferably 15 g / kg or more and 20 g / kg or less. In addition, the carbon black (C) preferably has a DBP absorption of 50 ml / 100 g or less. More preferably, it is 30 ml / 100 g or more and 50 ml / 100 g or less.

[0030] The total amount of (B) and (C) is preferably 60 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of (A). When the content is 60 parts by mass or more, the static spring constant is large and it is easy to achieve high rigidity. From this viewpoint, the content is more preferably 65 parts by mass or more, and even more preferably 70 parts by mass or more. On the other hand, when the content is 100 parts by mass or less, the dynamic spring constant is kept small in the high rigidity (large static spring constant) region, and it is easy to satisfy the low dynamic magnification in the high rigidity (large static spring constant) region. From this viewpoint, the content is more preferably 95 parts by mass or less, and even more preferably 90 parts by mass or less.

[0031] The mass ratio of the content of (C) to that of (B) is preferably 0.5 or more and 2.0 or less, from the viewpoints of achieving excellent low dynamic magnification in a high rigidity (large static spring constant) region and excellent durability.

[0032] The anti-vibration rubber composition according to the present invention may contain, in addition to the above-mentioned components (A) to (C), appropriate additives, etc. Examples of the additives include vulcanizing agents, vulcanization accelerators, vulcanization aids, antioxidants, process oils, etc.

[0033] Examples of the vulcanizing agent include sulfur (powdered sulfur, precipitated sulfur, insoluble sulfur), and sulfur-containing compounds such as alkylphenol disulfides, etc. These may be used alone or in combination of two or more kinds.

[0034] The content of the vulcanizing agent is preferably in the range of 0.1 to 10 parts by weight, particularly preferably in the range of 0.3 to 5 parts by weight, based on 100 parts by weight of the diene rubber (A). If the content of the vulcanizing agent is too low, crosslinking reactivity tends to deteriorate. If the content of the vulcanizing agent is too high, rubber physical properties (breaking strength, breaking elongation) tend to deteriorate.

[0035] Examples of the vulcanization accelerator include thiuram-based, sulfenamide-based, guanidine-based, thiazole-based, aldehyde ammonia-based, aldehyde amine-based, and thiourea-based vulcanization accelerators. These are used alone or in combination of two or more. Among these, a combination of a thiuram-based vulcanization accelerator and at least one vulcanization accelerator selected from the sulfenamide-based, guanidine-based, and thiazole-based vulcanization accelerators is preferred because it provides excellent compression set.

[0036] The content of the vulcanization accelerator is preferably in the range of 0.1 to 10 parts by weight, particularly preferably in the range of 0.3 to 5 parts by weight, based on 100 parts by weight of the diene rubber (A).

[0037] Examples of thiuram vulcanization accelerators include tetramethylthiuram disulfide (TMTD), tetraethylthiuram disulfide (TETD), tetrabutylthiuram disulfide (TBTD), tetrakis(2-ethylhexyl)thiuram disulfide (TOT), tetrabenzylthiuram disulfide (TBzTD), and the like.

[0038] Examples of sulfenamide vulcanization accelerators include N-oxydiethylene-2-benzothiazolylsulfenamide (NOBS), N-cyclohexyl-2-benzothiazolylsulfenamide (CBS), Nt-butyl-2-benzothiazolesulfenamide (BBS), N,N'-dicyclohexyl-2-benzothiazolesulfenamide, etc. These may be used alone or in combination of two or more kinds.

[0039] Examples of the guanidine vulcanization accelerator include N,N'-diphenylthiourea, trimethylthiourea, N,N'-diethylthiourea, N,N'-dibutylthiourea, etc. These may be used alone or in combination of two or more kinds.

[0040] Examples of thiazole-based vulcanization accelerators include dibenzothiazyl disulfide (MBTS), 2-mercaptobenzothiazole (MBT), 2-mercaptobenzothiazole sodium salt (NaMBT), and 2-mercaptobenzothiazole zinc salt (ZnMBT). These are used alone or in combination of two or more. Among these, dibenzothiazyl disulfide (MBTS) and 2-mercaptobenzothiazole (MBT) are preferably used because of their excellent crosslinking reactivity.

[0041] Examples of the vulcanization aid include zinc oxide (ZnO), stearic acid, magnesium oxide, etc. These may be used alone or in combination of two or more kinds.

[0042] The content of the vulcanization aid is preferably in the range of 0.1 to 10 parts by weight, particularly preferably in the range of 0.3 to 7 parts by weight, based on 100 parts by weight of the diene rubber (A).

[0043] Examples of the antiaging agent include carbamate-based antiaging agents, phenylenediamine-based antiaging agents, phenol-based antiaging agents, diphenylamine-based antiaging agents, quinoline-based antiaging agents, imidazole-based antiaging agents, waxes, etc. These may be used alone or in combination of two or more kinds.

[0044] The content of the antioxidant is preferably in the range of 0.5 to 15 parts by weight, and particularly preferably in the range of 1 to 10 parts by weight, based on 100 parts by weight of the diene rubber (A).

[0045] Examples of process oils include naphthenic oils, paraffinic oils, aromatic oils, etc. These may be used alone or in combination of two or more.

[0046] The content of the process oil is preferably in the range of 1 to 35 parts by weight, particularly preferably in the range of 3 to 30 parts by weight, based on 100 parts by weight of the diene rubber (A).

[0047] The anti-vibration rubber composition according to the present invention can be prepared by kneading the components (A) to (C) and other materials added as necessary using a kneading machine such as a kneader, a Banbury mixer, an open roll, or a twin-screw mixer.

[0048] The anti-vibration rubber composition according to the present invention becomes an anti-vibration rubber member (vulcanizate) by vulcanizing at high temperature (150 to 170°C) for 5 to 30 minutes. The anti-vibration rubber member made of the vulcanizate of the anti-vibration rubber composition according to the present invention can be advantageously used in applications such as motor mounts, suspension bushes, subframe mounts, and other anti-vibration rubbers for electric vehicles (including electric vehicles (EV), fuel cell vehicles (FCV), plug-in hybrid vehicles (PHV), hybrid vehicles (HV), and the like) that use electric motors as their power source.

[0049] According to the vibration-proof rubber composition of the present invention having the above-mentioned configuration, since the diene rubber (A) is blended with the surface-active carbon black (B) and the carbon black (C) having an iodine adsorption amount of 20 g / kg or less, it is possible to achieve a low dynamic magnification in the high rigidity (large static spring constant) range.

[0050] In the anti-vibration rubber composition according to the present invention, from the viewpoint of suitability for electric vehicles, the static spring constant Ks is preferably 700 N / mm or more and 1000 N / mm or less. More preferably, it is 750 N / mm or more and 1000 N / mm or less. By configuring the anti-vibration rubber composition according to the present invention as described above, the static spring constant Ks can be set within the above range.

[0051] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the spirit of the present invention. EXAMPLES

[0052] The present invention will be described in detail below using examples and comparative examples.

[0053] The materials used are as follows: <Diene rubber (A)> Natural rubber (NR) Terminally modified butadiene rubber (terminally modified BR): Modifier: ε-caprolactam, polymer viscosity: 50, cis-1,4 / trans-1,4 / vinyl ratio = 39 / 49 / 12 <Surface active carbon black (B)> Surface-active carbon black (surface-active CB): SPHERON5200 manufactured by Cabot Japan (Hc: 5200ppm, iodine adsorption 24g / kg, DBP absorption 124ml / 100g) <Carbon black (C)> ·CB <1> : Tokai Carbon's "Seast TA", iodine adsorption capacity 18g / kg, DBP absorption capacity 42ml / 100g) <Other> ·CB <2> : Tokai Carbon's "Seast SO", iodine adsorption capacity 44g / kg, DBP absorption capacity 115ml / 100g) Zinc oxide: Sakai Chemical Industry's "Zinc oxide type 2" Stearic acid: Kao's "Lunacc S30" Process oil: Sansen 4130 made by Nippon San Oil Amine-based antioxidants <1> : Seiko Chemical's "Ozonone 6C" Amine-based antioxidants <2> : "Nonflex RD" manufactured by Seiko Chemical ·Vulcanization accelerator <1> : "Noccela CZ" manufactured by Ouchi Shinko Chemical ·Vulcanization accelerator <2> : "Noccela TBT" manufactured by Ouchi Shinko Chemical Sulfur (vulcanizing agent)

[0054] (Examples 1 to 4, Comparative Examples 1 to 3) The materials were mixed in the ratios (parts by mass) shown in the table, and then mixed using an internal mixer (Banbury type) or rolls to prepare rubber compositions. The properties of the prepared rubber compositions were measured and evaluated according to the following methods.

[0055] [Static spring constant (Ks)] Using each rubber composition, a rubber test piece was prepared by pressing and vulcanizing a disk-shaped metal fitting (diameter 60 mm, thickness 6 mm) onto the top and bottom surfaces of a rubber piece (diameter 50 mm, height 25 mm) under vulcanization conditions of 170°C x 30 minutes. Next, the rubber test piece was compressed 7 mm in the cylindrical axial direction, and the loads at deflections of 1.5 mm and 3.5 mm were read from the load-deflection curve of the second forward movement to calculate the static spring constant (Ks (N / mm)).

[0056] [Dynamic spring constant (Kd100)] The rubber test piece was compressed by 2.5 mm in the cylindrical axial direction, and a constant displacement harmonic compression vibration with an amplitude of 0.05 mm and a frequency of 100 Hz was applied from below centered on the position of this 2.5 mm compression. The dynamic load was detected by a load cell above, and the dynamic spring constant (Kd100 (N / mm)) was calculated in accordance with JIS K 6394.

[0057] [Dynamic magnification (Kd100 / Ks)] The dynamic magnification was calculated as the value of dynamic spring constant (Kd100) / static spring constant (Ks). Since the dynamic magnification is proportional to Ks, a rubber material with a lower dynamic magnification is preferable when the Ks is the same. Therefore, the dynamic magnification was evaluated (comparison of the superiority of the dynamic magnification) using the value obtained by dividing the dynamic magnification by Ks. Values ​​of [dynamic magnification / Ks×1000] of 1.90 or less were evaluated as "○", and those exceeding 1.90 were evaluated as "×".

[0058] [Durability] Each rubber composition was press molded (vulcanized) at 150°C for 30 minutes to produce a rubber sheet with a thickness of 2 mm. Then, a JIS No. 3 dumbbell was punched out from this rubber sheet, and a stretch fatigue test was performed using this dumbbell in accordance with JIS K 6260 to measure the number of times of durability. Those that had a durability of more than 4000 times were rated "A", those that had a durability of 2000 times or more and 4000 times or less were rated "B", and those that had a durability of less than 2000 times were rated "C".

[0059] [Table 1]

[0060] In Comparative Examples 1 and 3, no surface-active carbon black is blended with the diene rubber. In Comparative Example 1, only one type of non-surface-active carbon black is blended with the diene rubber. In Comparative Example 3, two types of non-surface-active carbon black are blended with the diene rubber. In Comparative Example 2, surface-active carbon black and non-surface-active carbon black are blended with the diene rubber, but the non-surface-active carbon black does not have an iodine adsorption amount of 20 g / kg or less. According to the Comparative Examples, none of the Comparative Examples achieves a low dynamic magnification in the high rigidity (large static spring constant) region.

[0061] In contrast, in the examples, surface active carbon black and carbon black with an iodine adsorption of 20 g / kg or less are blended with the diene rubber, achieving a low dynamic magnification in the high rigidity (large static spring constant) range.

[0062] From the above examples and comparative examples, it is clear that by blending surface active carbon black (B) and carbon black (C) having an iodine adsorption amount of 20 g / kg or less with diene rubber (A), it is possible to achieve a low dynamic magnification in the high rigidity (large static spring constant) range.

[0063] Among the examples, it is seen that when the mass ratio of the content of carbon black (C) to the content of surface active carbon black (B) is 0.5 or more and 2.0 or less, superior durability is achieved.

[0064] Although the embodiments and examples of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible without departing from the spirit and scope of the present invention.

Claims

1. The anti-vibration rubber composition for electric vehicles comprises the following components (A) to (C): (A) Diene rubber (B) A surface active carbon black having an amount of hydrogen generated when heated to 1980° C. per gram of carbon black (Hc) of 4500 ppm or more. (C) Carbon black having an iodine adsorption amount of 20 g / kg or less

2. 2. The anti-vibration rubber composition for electric vehicles according to claim 1, wherein the total amount of (B) and (C) is 60 parts by mass or more and 100 parts by mass or less per 100 parts by mass of (A).

3. 3. The anti-vibration rubber composition for electric vehicles according to claim 1, wherein a mass ratio of the content of said (C) to the content of said (B) is 0.5 or more and 2.0 or less.

4. 3. The anti-vibration rubber composition for electric vehicles according to claim 1, wherein the (A) is one or more rubbers selected from the group consisting of natural rubber, butadiene rubber, styrene-butadiene rubber, isoprene rubber, and chloroprene rubber.

5. 3. The anti-vibration rubber composition for electric vehicles according to claim 1, wherein the static spring constant Ks is 700 N / mm or more and 1000 N / mm or less.

6. The total amount of (B) and (C) is 60 parts by mass or more and 100 parts by mass or less with respect to 100 parts by mass of (A), The mass ratio of the content of (C) to the content of (B) is 0.5 or more and 2.0 or less, The (A) is one or more rubbers selected from natural rubber, butadiene rubber, styrene-butadiene rubber, isoprene rubber, and chloroprene rubber, 2. The anti-vibration rubber composition for electric vehicles according to claim 1, having a static spring constant Ks of 700 N / mm or more and 1000 N / mm or less.

7. 2. An anti-vibration rubber member for electric vehicles, comprising a vulcanizate of the anti-vibration rubber composition for electric vehicles according to claim 1.

Citation Information

Patent Citations

  • Anti-vibration rubber composition for electric vehicles and anti-vibration rubber member for electric vehicles

    JP7037986B2